Parents and teachers as partners : issues and challenges - Rockwell, Robert E.; Andre, Lynda C.; Hawley, Mary K. (Fort Worth, TX : Harcourt Brace, 1996)
This book is divided into three parts: Issues and Challenges; Communication; and Support for Partnership between Parents and Teachers.
Keywords: Education; United States; Parent-teacher relationships -- United States; Home and school -- United States